Trichophorum polygamum, a replacement name for Korean Scirpus dioicus (Cyperaceae) - Son, Dong Chan; Kim, Nak Yong; Chang, Kae Sun (Phytotaxa, 2019)
A replacement name Neoscirpus dioicus Y.N.Lee & Y.C.Oh (2006b: 25) was published for the illegitimate Scripus dioicus Y.N.Lee & Y.C.Oh (2006a: 614), a name that applies to an endemic sedge occurring in limestone areas of the Gangwon-do Province, Republic of Korea (Park et al. 2016, Chung et al. 2017).